Influence of some physico-chemical factors on properties of electrodes that decompose water catalytically - Primachenko, V.E.; Serba, O.A.; Chernobai, V.A.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
We have investigated the current creation accompanied by the water decomposition H₂O → OH + H caused by various catalytically active electrodes with different electrochemical potentials, both without external electric voltage on these electrodes and with the applied voltage V₀ = ±9.7 V. It is found that the current value and its time dependence are essentially influenced by such factors as thermal and natural (in ambient atmosphere) oxidation of electrodes (made of Al, Si, Yb, Ni, Ti, Cr₃Si, and Ni₃Si), changing their relief (texturing, polishing), and the electrolytic deposition of palladium as an impurity on the surface (Ti, Cr₃Si). Changes in the current caused by the above factors are realized as a consequence of changes in both the electron work function inherent to these electrodes and their catalytical activity concerning the water decomposition both in the absence and the presence of the external voltage V₀.